Cattle colonialism an environmental history of the conquest of California and Hawai'i - Fischer, John Ryan (Flows, migrations, and exchanges, 2015)
"Environmental historians have too often overlooked California and Hawai'i, despite the roles the regions played in the colonial ranching frontiers of the Pacific World. In Cattle Colonialism, John Ryan Fischer significantly enlarges the scope of the American West by examining the trans-Pacific transformations these animals wrought on local landscapes and native economies" --